1993
DOI: 10.1016/0550-3213(93)90041-m
|View full text |Cite
|
Sign up to set email alerts
|

Duality symmetries from non-abelian isometries in string theory

Abstract: In string theory it is known that abelian isometries in the σ-model lead to target space duality. We generalize this duality to backgrounds with non-abelian isometries. The procedure we follow consists of gauging the isometries of the original action and constraining the field strength F to vanish. This new action generates dual theories by integrating over either the Lagrange multipliers that set F = 0 or the gauge fields. We find that this new duality transformation maps spaces with non-abelian isometries to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
728
0
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 396 publications
(745 citation statements)
references
References 42 publications
16
728
0
1
Order By: Relevance
“…The results of [28] suggest that T-duality should generalise to this case, but the non-abelian structure leads to issues similar to those that arise in non-abelian duality [36], [37], [38], so that the approach used here appears difficult to implement in that case.…”
Section: T-folds and T-dualitymentioning
confidence: 95%
“…The results of [28] suggest that T-duality should generalise to this case, but the non-abelian structure leads to issues similar to those that arise in non-abelian duality [36], [37], [38], so that the approach used here appears difficult to implement in that case.…”
Section: T-folds and T-dualitymentioning
confidence: 95%
“…Consider the σ-model action (1) and assume that the target space metric has a group G of non-abelian isometries [10], [33], [34], [35]. In this case, Q MN does depend on X m and transforms accordingly under X m → g m n X n , g ∈ G. We gauge the symmetry corresponding to a subgroup…”
Section: Non-abelian T -Dualitymentioning
confidence: 99%
“…Later on, this duality was understood in terms of the standard duality of 2D non-linear sigma models studied in supergravity [8] , [9] and it was extended to more general backgrounds, including backgrounds with non-abelian isometries [10]. Duality originating from symmetries of the string 2D sigma model is presently known as T -duality.…”
Section: Introductionmentioning
confidence: 99%
“…The correct dual model was first found by Fridling and Jevicki [6] and Fradkin and Tseytlin [7] using path integral methods. String theory motivated a renewed interest in abelian and nonabelian duality [8,9,10,11,12,13,14,15]. It was shown that the duality transformation was canonical [16,17] and these ideas were generalized in a variety of ways [18,19,20,21,22].…”
Section: Introductionmentioning
confidence: 99%